2015
DOI: 10.1002/erv.2394
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Intervention on Physical Activity and Sedentary Behaviours in Bariatric Surgery Patients: Emphasis on Mobile Technology

Abstract: Physical activity (PA) and sedentary behaviors (SB—i.e. activities involving low energy expenditure and a sitting/reclining posture) may each have significant implications for weight loss and other bariatric surgery outcomes. While early studies suggested that patients typically comply with clinical recommendations to adopt habitual PA, these data were based on retrospective questionnaires. Conversely, recent studies incorporating mobile health (mHealth) technologies (e.g., objective monitors), which assess PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 42 publications
(79 reference statements)
0
31
0
Order By: Relevance
“…Given that postoperative patients did not show higher PA compared to preoperative patients and that both groups showed a rather low PA level, special emphasis should be placed on increasing PA in pre-and postoperative care programs. In addition to traditional face-to-face interventions, personalized adaptive interventions via mobile health (mHealth) technologies could be used to enhance PA in pre-as well postoperative bariatric surgery patients [69,70]. Future studies are needed to investigate whether interactive monitoring and adaptive shaping are effective in the improvement of PA in this patient group.…”
Section: Resultsmentioning
confidence: 97%
“…Given that postoperative patients did not show higher PA compared to preoperative patients and that both groups showed a rather low PA level, special emphasis should be placed on increasing PA in pre-and postoperative care programs. In addition to traditional face-to-face interventions, personalized adaptive interventions via mobile health (mHealth) technologies could be used to enhance PA in pre-as well postoperative bariatric surgery patients [69,70]. Future studies are needed to investigate whether interactive monitoring and adaptive shaping are effective in the improvement of PA in this patient group.…”
Section: Resultsmentioning
confidence: 97%
“…Identifying effective strategies for increasing MVPA in BS patients is important given that the vast majority are inactive preoperatively and bariatric surgery has shown to have limited if any impact on MVPA levels postoperatively. 25 Further, morning exercise may help to counter perceived lack of time, a frequently reported barrier to PA participation in BS patients and one which is unlikely to be affected by weight loss and other surgical outcomes. 7,8 …”
Section: Discussionmentioning
confidence: 99%
“…1,2 Further, approximately two-thirds of BS patients do not perform any bout-related MVPA. 35 Efforts to increase bout-related MVPA in BS patients preoperatively are needed given that most patients fail to make substantial MVPA changes postoperatively, 4,5 and higher preoperative MVPA strongly predicts higher postoperative PA. 1,6 One common obstacle to habitual MVPA adoption in obese populations, including BS patients, is perceived lack of time.…”
mentioning
confidence: 99%
“…Patients attending routine clinical appointments and patient support groups often mention using social media and technology to health care practitioners, but no studies were found which examined how practitioners engage with patient-led social media and mobile apps. There is also a dearth of information and the use of technology such as telehealth and videoconferencing in routine bariatric surgical patient care pre and post-operatively (6,7). No studies were found which explored the use of social media with bariatric surgical patients.…”
Section: Introductionmentioning
confidence: 99%